Mitochondrial DNA content and function, childhood obesity, and insulin resistance. (2nd January 2016) - Shoar, Zohreh; Goldenthal, Michael J.; De Luca, Francesco; Suarez, Elizabeth
Abstract: Objectives : The objectives of our study were to compare the mitochondrial enzyme activity between obese and non-obese children and to assess the association between mitochondrial DNA content and function and markers of metabolic syndrome. Methods : Clinical and anthropometric data of obese and normal-weight children ages 2–18 years were collected. We collected buccal swabs for mitochondrial respiratory enzymes (complex I, IV, and Citrate Synthase). In obese children only, serum levels of metabolic parameters and mitochondrial DNA from mononuclear cells were quantitated. Results : We recruited 75 obese and 65 normal-weight children. There was no difference in respiratory complex enzyme activity levels between obese and normal-weight subjects. In obese subjects, mitochondrial to nuclear DNA (mt/nDNA) ratio was significantly correlated with BMI Z -score and BMI percentile ( p < 0.05, and p < 0.01, respectively), and the strength of this correlation was proportionate to the degree of obesity. We did not find any association between mt/nDNA ratio and metabolic parameters. We observed a significant positive association between complex IV activity and fasting insulin level ( p < 0.05). Finally, fasting insulin explained 45% of the variation in the complex IV activity level ( p < 0.05). Conclusion : Our findings indicate that mitochondrial DNA content is directly related to obesity, but not to the markers of metabolic syndrome/insulin resistance in children. Longitudinal studies involving larger samples are needed to confirm our findings and help elucidate the relationship between mitochondrial function, adiposity, and insulin resistance.